Patron Gods and Patron Lords : The Semiotics of Classic Maya Community Cults - Baron, Joanne (Book collections on Project MUSE., 2016)
"Baron demonstrates the central importance of patron deity cults in political relationships between both rulers and their subjects and different Maya kingdoms. Weaving together evidence from inscriptions, images, and artifacts"--Provided by publisher.